2018
DOI: 10.1111/asj.12983
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Polish Arabian horses assessed through breeding and microsatellite data

Abstract: Polish Arabian horses are one of the most important populations of this breed in the world. Their post-war history can be divided into two periods, with the dominant role of state studs until 1989, and the increasing significance of private breeding in the next years. The goal of the study was to evaluate genetic diversity and structure of the population under a new breeding policy. The analyses of breeding and microsatellite data from 1996 to 2012 provide a coherent picture of the population with constant flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In the last period, the alleles identified were six, but two were private and rare (HTG7/P 0.08% and HTG7/Q 0.05%), a consequence of the introduction of two mares ( Table S6 ). HTG7/L identified since the first period (3.7%) decreased to the last period, where it was missing, similarly to what was described by Glazewska et al, 2018 [ 32 ] in Polish Arabian horses because of breeding selection.…”
Section: Discussionsupporting
confidence: 81%
“…In the last period, the alleles identified were six, but two were private and rare (HTG7/P 0.08% and HTG7/Q 0.05%), a consequence of the introduction of two mares ( Table S6 ). HTG7/L identified since the first period (3.7%) decreased to the last period, where it was missing, similarly to what was described by Glazewska et al, 2018 [ 32 ] in Polish Arabian horses because of breeding selection.…”
Section: Discussionsupporting
confidence: 81%
“…Due to the lack of recombination and its uniparental inheritance, mitochondrial DNA (mtDNA) is extensively used to genetically distinguish one dam line from another and to trace ancestry through the maternal lineage of a pedigree. Głażewska et al [11] have demonstrated the usefulness of pedigree data in genetic diversity studies, allowing a focused animal sampling and rare haplotypes identification. On the other hand, many scholars verified the reliability of the maternal lineages recorded in the Studbooks through mitochondrial diversity surveys [10,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven microsatellite markers (AHT4, ASB2, HMS2, HMS3, HMS6, HMS7, HTG4, HTG6, HTG7, HTG10, VHL20) were included, i.e. the same set as in our previous publication (Głażewska et al, 2018). Currently, a greater number of markers is used in parentage control than was used initially.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…The present study is a continuation of our previous work (Głażewska et al, 2018) on the genetic diversity of state and private Polish Arabian horses used in breeding between 1996 and 2012 which was examined with breeding and microsatellite data. The goal of that study was to evaluate the genetic diversity of the population under the new breeding policy in Poland after 1989 which encouraged the development of private breeding and enabled significant imports of breeding material from other countries.…”
mentioning
confidence: 96%
See 1 more Smart Citation